Epigenetics and the IRFs: A complex interplay in the control of immunity and autoimmunity. (11th November 2013) - Rogatsky, Inez; Chandrasekaran, Uma; Manni, Michela; Yi, Woelsung; Pernis, Alessandra B.
Abstract: Effective immune responses require the coordinated activation and differentiation of several cell types, including T-cells, B-cells and myeloid cells. Abnormalities in the appropriate regulation of these processes underlie the pathogenesis of many autoimmune disorders, including systemic lupus erythematosus (SLE). Recent studies have revealed that, in addition to sequence-specific DNA-binding factors, the chromatin landscape of a cell can play a pivotal role in controlling these processes and in regulating the onset of autoimmunity. Interferon regulatory factors (IRFs) are emerging as critical regulators of the activation and differentiation of immune cells and deregulation in the expression and/or function of members of the IRF family has increasingly been linked to the pathogenesis of lupus. In this review, we will provide a brief overview of the role of different IRFs in immune responses and SLE development and discuss studies, which highlight the intricate relationship of this family of transcription factors with the epigenetic machinery.